Geochemical Exploration for Metallic Minerals in the Meta-Sedimentary Rocks of Ogotun, Ikeji-Ile and Ipetu, Southwestern Nigeria - Ige, Olususi Joseph; Samuel, Ayodele Olusiji; Ominyi, Ajigo Isaac (International Journal of Geography and Geology, 2022)
The south-eastern part of Ilesha Schist belt which comprises of (Ogotun,Ikeji-Ile and Ipetu-the study area has been totally neglected by previous researchers without any literatures that could serve as clues to mineral exploration in the study area which necessitate this research. Geological mapping was undertaken to determine the underlying rocks followed by systematic sampling at one rock per 3.25km2, petrographic and geochemical analysis of the rocks. The results of field examination confirmed the existence of migmatite-gneisses, quartzites, quartz-schists, meta-conglomerates and porphyritic granites as the dominant rocks while petrographic studies revealed quartz, biotite, feldspar (microcline and plagioclase) and opaque minerals. However, five rocks samples whose thin sections showed opaque minerals were viewed under the reflecting light microscope and a brassy yellow mineral called chalcopyrite was confirmed. Geochemical analytical results revealed that SiO2 (67.37%-62.46%) and Al2O3 (17.35%-11.62%) have higher concentrations, indicating the aluminosilicate nature of the rocks. The trace elemental analysis revealed very high concentrations of Ba (2533-10) ppm and Fe (55000-4100) ppm, followed by moderate to low and very low concentrations of Cu (38.40-12.50) ppm, Pb (.90-39.40) ppm, Zn (156.00-7.00) ppm, Co (65.20-1.40) ppm, Mn (148.00-981.00) ppm,, As (1.00-3.00) ppm, Th (0.50-10.00) ppm, Rb (311.60-50) ppm ,Cr (1310.-5.00) ppm and U (>0.1-6.3) ppm. Similarly, the principal component analysis (PCA) of the rocks revealed Cu-Pb-Zn-Mn-Fe mineral associations with 35.24% also confirmed massive sulphide mineralization. Therefore, the overall results indicated the potentials of the study area to be possibly enriched with other hidden ore deposits and radioactive minerals.